2019
DOI: 10.9745/ghsp-d-18-00287
|View full text |Cite
|
Sign up to set email alerts
|

Community Perspectives of a 3-Delays Model Intervention: A Qualitative Evaluation of Saving Mothers, Giving Life in Zambia

Abstract: While the Saving Mothers, Giving Life's health systems strengthening approach reduced maternal mortality, respondents still reported significant barriers accessing maternal health services. More research is needed to understand the necessary intervention package to affect system-wide change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…The plan was endorsed by the SMGL Leadership Council members who also pledged funding for executing the plan. Using 2016 as the index year for SMGL final results, end-of-initiative studies were undertaken in 2017 to establish outcomes in the learning districts: (1) a census in Zambia and a RAMOS in Uganda, 38 , 48 (2) repeat HFAs in all delivering facilities in the learning districts, 38 (3) a cost-effectiveness study addressing the 3 delays, 7 (4) a secondary analysis comparing SMGL district outcomes with findings from the Uganda Demographic and Health Survey (DHS) in comparison districts and nationally, 31 (5) a follow-on qualitative study of community perspectives on childbearing in Zambia, 49 and (6) a repeat travel-time mapping study in Uganda to gauge if the SMGL initiative resulted in greater access to care 50 …”
Section: Project Design Implementation and Assessmentmentioning
confidence: 99%
“…The plan was endorsed by the SMGL Leadership Council members who also pledged funding for executing the plan. Using 2016 as the index year for SMGL final results, end-of-initiative studies were undertaken in 2017 to establish outcomes in the learning districts: (1) a census in Zambia and a RAMOS in Uganda, 38 , 48 (2) repeat HFAs in all delivering facilities in the learning districts, 38 (3) a cost-effectiveness study addressing the 3 delays, 7 (4) a secondary analysis comparing SMGL district outcomes with findings from the Uganda Demographic and Health Survey (DHS) in comparison districts and nationally, 31 (5) a follow-on qualitative study of community perspectives on childbearing in Zambia, 49 and (6) a repeat travel-time mapping study in Uganda to gauge if the SMGL initiative resulted in greater access to care 50 …”
Section: Project Design Implementation and Assessmentmentioning
confidence: 99%
“… Article 7: Saving Lives Together: A Qualitative Evaluation of the Saving Mothers, Giving Life Public-Private Partnership 9 Article 8: Community Perceptions of a 3-Delays Model Intervention: A Qualitative Evaluation of Saving Mothers, Giving Life in Zambia 10 Article 9: Did Saving Mothers, Giving Life Expand Timely Access to Lifesaving Care in Uganda?…”
Section: What Was Accomplished?mentioning
confidence: 99%
“…Article 8: Community Perceptions of a 3-Delays Model Intervention: A Qualitative Evaluation of Saving Mothers, Giving Life in Zambia 10 …”
Section: What Was Accomplished?mentioning
confidence: 99%
“…Near miss is a multifactorial condition which is caused by socio-economic, health event, skill of health care providers, and sub-standardized services [1113]. Studies indicated that low socioeconomic status, unemployment, high parity, being single, and prior caesarean section are predictors of maternal near misses [14, 15]. The three delays are the main cause for maternal near miss [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…The second delay is related to delay in reaching health facility due to lack of access, transport problem, and cost related issues. While, the third delay is delay in receiving care due to either lack of trained personnel, equipments or poor quality of care [15].…”
Section: Introductionmentioning
confidence: 99%